The Hip and Pelvis in Sports Medicine and Primary Care - Seidenberg MD, FAAFP, FACSM, RMSK, Peter H.; Bowen MD, FAAPMR, CAQSM, RMSK, CSCS, Jimmy D.; King MD, David J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Now in a revised and updated second edition, this practical guide remains an invaluable resource for improving the management of hip and pelvis injuries and presents a spectrum of treatment options for children, adolescents, adults and special populations. Opening with valuable clinical pearls for each topic, differential diagnosis is emphasized throughout the chapters, and evidence-based guidelines and sport-specific considerations aid the reader with injury evaluation and care. From fundamentals$1 (Bincluding epidemiology, history and physical examination, imaging and gait assessment$1 (Bto functional therapeutic interventions, injection techniques, taping and bracing, and both surgical and non-surgical interventions, The Hip and Pelvis in Sports Medicine and Primary Care, Second Edition is ideal for sports medicine physicians, primary care physicians, physical therapists and athletic trainers alike.s
Epidemiology of Hip and Pelvis Injury -- Physical Examination of the Hip and Pelvis -- Functional and Kinetic Chain Evaluation of the Hip and Pelvis -- Gait Assessment -- Radiology of Hip Injuries -- Adult Hip and Pelvis Disorders.-Hip and Pelvis Injuries in Childhood and Adolescence -- Specific Considerations in Geriatric Athletes -- Hip and Pelvis Injuries in Special Populations -- Functional Therapeutic and Core Strengthening -- Manual Medicine of the Hip and Pelvis -- Taping and Bracing for Pelvic and Hip Injuries -- Nonsurgical Interventions -- Treatment Options for Degenerative Joint Disease of the Hip -- Surgical Interventions in Hip and Pelvis Injuries. .
Keywords: Medicine; Orthopedics; Primary care (Medicine).; Sports medicine; Medicine & Public Health; Sports medicine; Primary Care Medicine; Orthopedics